Effect of sodium thiosulfate irrigation on push-out bond strength of root canal obturation material - Panjiswastiawan, Leonardo Radito; Mulyawati, Ema; Kristanti, Yulita (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Sodium hypochlorite is used as irrigation solution during root canal preparation because of its antibacterial effect. However, it degrades dentinal collagen and generates oxygen free layer on dentin surfaces that might prevent penetration of sealer. Sodium thiosulfate is an antioxidant and has been reported to neutralize that side effect. The objective of this study was to determine the effect of concentration and application time of sodium thiosulfate irrigation on push-out bond strength of root canal obturation material. This study used extracted human mandibular premolars single root post extraction. The root canals were prepared using crown down technique up to file F3. The samples were divided into four groups. Groups IA and IB were irrigated with sodium thiosulfate 5% for 3 and 5 minutes, while Groups IIA and IIB were irrigated with sodium thiosulfate 10% for 3 and 5 minutes. The control group was irrigated with saline for 3 and 5 minutes. The root canals were obturated with epoxy resin sealer and gutta percha, and were incubated for 7 days. Samples were horizontally sectioned into 2 mm thickness in apical third and were tested with push-out technique using universal testing machine. The adherence failure of samples was observed using stereo microscope. Data were analyzed with two-way ANOVA. There was a significant effect between concentration of sodium thiosulfate on push-out bond strength (p < 0.05), but application time showed the same effect (p > 0.05). The application of antioxidant resulted in an increase in the push-out bond strength of root canal obturation material, with 10% sodium thiosulfate demonstrating the highest push-out bond strength.